Factores familiares, sociales y emocionales presentes en tres jóvenes entre 11 y 13 años. Victimarios de Bullying en la institución educativa Nuestra Señora de Chiquinquirá en el municipio de Roldanillo Valle. (2023)
Bullying or better known as bullying has become a social, personal and family problem and has not only manifested itself during this time but also for several years in different ways and in different contexts for each person. It is referenced that bullying is one of the most frequent types of violence that can be found in schools and affects the comprehensive well-being of students, producing negative consequences for the victims. Of the most relevant authors that are mentioned throughout this project, they take the roles that bullying has as prevalence and in this we can find roles of aggressors, victims and observers and for that reason the interest arises to carry out a study which helps us to identify which are the Family, Social and Emotional factors present in three young people between 11 and 13 years old. Bullying perpetrators in an educational institution in the municipality of Roldanillo Valle; According to the results obtained in this project, it can be concluded that in the evaluated institution there is an average prevalence of bullying, which in some way is an alarm sign since the roads of both the victims and the victims may be at risk. of the victimizer It was also possible to observe that the perpetrator or perpetrators of bullying that were interviewed come from unstructured families, which various authors mentioned add that the role of the family within the performance of bullying is essential. Finally, it is suggested to carry out studies to determine exactly the behaviors that lead to the production of bullying in order to have a more extensive panorama about what is happening and to visualize more carefully the problems that this is generating within the institution.